The EU as an Actor of Normative Power in the Western Balkans After 2018: The Case of Kosovo, Albania and North Macedonia - Klodiana Beshku (Richtmann Publishing, 2023)
This article aims to examine the capacity of the European Union (EU) to continue to promote its normative power through the implementation of its Enlargement policy in the region of the Western Balkans. First, it examines the EU strategy towards the Western Balkans regarding its Enlargement Policy and the repercussion on the Western Balkans' perception of the European Union, which here is used as one of the denominators for the EU as a normative power. Then, using the Kosovo, Albania and North Macedonia cases, the article determines whether the EU continues to be considered a normative factor in the Western Balkans. Finally, it explores how the more inclusive Enlargement Policy followed by a harshened Conditionality has affected the future of the Western Balkans Region in the EU. Furthermore, this analysis sheds light on how the EU’s strategic vision has altered regarding the Region of the WB and how this vision meets the WB's expectations. Following such an examination, both sides of the story are scrutinized in a comparative approach to establish if the EU remains a normative power for the Western Balkan countries, even after a long period of EU integration stagnation. Received: 26 January 2023 / Accepted: 28 February 2023 / Published: 06 March 2023